DEVELOPMENT OF THE LAW OF COMPLETE SYSTEMATIC LAND REGISTRATION (PTSL) AND EFFECT OF CONDUCT VALUESOF LAND BASED ON DIGNIFY JUSTICE IN THE DISTRICT OF KENDAL, CENTRAL JAVA - Desy Dwi Nurhayati Hartanti; Gunarto Gunarto; Amin Purnawan (Sultan Agung Notary Law Review, 2019)
Kendal is one of district in Central Java. In Central Java, there are 592 744 17 197 land parcels including land parcels village treasury (TKD). Of the entire field of the land, 76.7% of them (ie 455 193 fields) has been certified which of them is located in Kendal district. Certifying land based on existing data is not at 100% therefore needs to be continued registration of land in order to achieve legal certainty and reduce the incidence of land disputes that exist. In order to achieve legal certainty in a plot of land owned by someone, then the central government in Nawacita (President Ultimate Goal) which is 9 (nine) priority that takes precedence provide a program that allows people in the maintenance of the certificate. Land Registry Systematic Complete is a land registration activities for the first time conducted secacara simultaneously for all objects of land registration throughout the territory of the Republic of Indonesia in the territory of the village / village or other names that level with it, which involves the collection and determination of the truth of physical data and juridical data regarding one or several objects of registration of land for the purposes of registration.Keywords: Legal Development; PTSL; land; Justice dignified.